Evaluation of Optic Nerve Head Vessel Density in Glaucoma Patients After Unilateral Phacoemulsification Using Solix Optical Coherence Tomography Angiography: Long-Term Results - Eraslan, Numan; Özbaran, Meliha Ece (Cerrahpaşa Medical Journal, 2025)
Objective: To compare the optic nerve head vessel density (VD) between phakic and pseudophakic eyes in glaucoma patients who underwent unilateral cataract surgery. Methods: A total of 58 eyes of 29 glaucoma patients with unilateral phacoemulsification were included in the study. Preoperative intraocular pressure (IOP) and angle grade (according to Shaffer classification), as well as postoperative mean IOP, angle grade, retinal nerve fiber layer (RNFL) thickness, central corneal thickness (CCT), and peripapillary vessel density (VD) parameters were compared between phakic and pseudophakic eyes. VD measurements were obtained using the Solix optical coherence tomography angiography (OCT-A) device, which features a 17% wider radial peripapillary capillary (RPC) analysis area compared with the AngioVue system. All scans had signal strength index ≥6/10. The mean follow-up period was 42 months (range, 24-84 months). Results: Preoperative IOP, angle grade, axial length and postoperative CCT, RNFL thickness, endothelial cell density were similar between groups (P > .05). Postoperatively, pseudophakic eyes had significantly lower mean IOP (P = .001) and greater angle width (P = .008). Mean RPC VD—the predefined primary outcome— was significantly higher in pseudophakic eyes compared with phakic eyes (P = .001). Grid-based VD values were also increased, particularly in the superior sector (P = .009). Conclusion: The lower postoperative IOP and wider iridocorneal angle observed in pseudophakic eyes may contribute to improved optic nerve head perfusion and sustained enhancement of peripapillary microvascular density. These long-term paired-eye findings indicate potential microvascular benefits of pseudophakia, although their prognostic significance remains to be confirmed in future longitudinal studies. Cite this article as: Eraslan N, Özbaran ME. Evaluation of optic nerve head vessel density in glaucoma patients after unilateral phacoemulsification using solix optical coherence tomography angiography: long-term results. Cerrahpaşa Med J 2025, 49, 0072, doi:10.5152/cjm.2025.25072.